الحماية القانونية لبراءة االختراع في التشريع الجزائري - عبلي شروق (المسيلة, 2023)
تعتبر براءة االختراع تعتبر من أهم عناصر الملكية الصناعية، لذا اهتمت أغلب الدول بتنظيمها الذي أصدر األمر 07-03 لمتعلق ببراءة االختراع، الذي يحدد الشروط الجزائري قانونيا على غرار المشرع الشكلية والموضوعية الواجب توافرها في االختراع حتى يستحق البراءة من طرف الهيئة المختصة؛ وهي للملكية الصناعية، ويترتب على عاتق مالل براءة االختراع حقوق والتزامات كحقه الجزائري المعهد الوطني باستغالل براءته، أو التصرف فيها. حماية لحق المخترع من التعدي، بأن منح له حق رفع دعويين األولى الجزائري وقد وفر المشرع مدنية أصلية، والثانية جزائية ضد جرم تقليد اختراعه، أما بالنسبة للحماية الدولية فتمثلت في مختلف االتفاقيات الدولية التي صادقت عليها الجزائر وعدلت بموجبها تشريعها المتعلق بحماية االختراع، فأصدرت األمر 07-03 المتعلق ببراءة االختراع، ورغم مالئمة قانون براءة االختراع للمتطلبات االقتصادية المستجدة وأخذه بالمعايير الحديثة، إال أن ما يعاب عليه تركه لبعف الثغرات القانونية. : الحماية القانونية، براءة االختراع، التشريع الجزائري. الكلمات المفتاحية Summary: The patent is considered to be one of the most important elements of industrial property. Therefore, most States have taken an interest in regulating it legally along the lines of Algerian legislation, which issued order 03-07 on the patent, which sets forth the formal and objective conditions to be met in the patent so that it may be patented by the competent body; It is the Algerian National Institute of Industrial Property, and the patent owner has rights and obligations to exploit or dispose of his or her patent. The Algerian legislature protected the inventor's right against infringement by granting the inventor the right to lodge two initial civil claims, The second is punitive against the offence of the tradition of inventing it. With regard to international protection, it is represented in the various international conventions ratified by Algeria and amended its legislation on the protection of the invention. It issued Order 03-07 on Patent, although the Patent Act is appropriate to emerging economic requirements and takes it into account modern standards, it has some legal gaps. Keywords: legal protection, patent, Algerian legislation
Keywords: الحماية القانونية، براءة االختراع، التشريع الجزائري